Boosting the activity in the liquid-phase hydrogenation of S-containing nitroarenes by dual-site Pt/CeO2 catalysts design - Xiaomin Ren; Jiayi Huang; Jun Ma; Yimo Zhang; Wei Chu; Siglinda Perathoner; Gabriele Centi; Yuefeng Liu (Nature Communications)
Abstract The liquid phase hydrogenation of nitroarenes is an important industrial reaction. The active sites are typically supported metal nanoparticles, which can be easily deactivated when sulfur groups are present in the substrate. Here, we report a new strategy for converting these S-containing nitroarenes by developing a dual-sites Pt/CeO2 catalyst consisting of highly defective CeO2 with abundant active oxygen vacancy and Pt sub-nano clusters. The hydrogenation of the nitro group in S-containing nitroarenes is induced to occur on the oxygen vacancies of the support rather than on the metal nanoparticles, which act only as the site of activating H2 by spillover. This functionality is not inhibited by strong chemisorption of the reactant S-groups, which is different from the hydrogenation of the nitro groups. Spillover H migrates to the oxygen vacancy site on the surface of defective CeO2, where the nitro-group is activated and reduced. This unconventional mechanism of hydrogenation is proven by combining many characterizations, theoretical modelling, kinetic and poisoning experiments. The best Pt/CeO2-300 catalyst shows a high reaction rate of 3.9 mmol·gcat. −1·h−1 with 5-amino benzothiazole selectivity of > 99%. It could produce over 145 kg·kgPt −1 of pure 5-amino benzothiazole in 250 hours on stream under continuous flow conditions. It is also proven and quantified by studying several molecules with different sizes and electronic structures that the accessibility of the -NO2 group to the Pt surface determines where the nitro groups are hydrogenated. Larger conjugated structures inhibit accessibility to the Pt surface of the -NO2 group, making it more prone to vacancy-activated nitro groups. This study provides valuable insights into the rational design and precise development of catalysts for the hydrogenation of liquid-phase chemicals containing S-groups.